Activation of Aryl Hydrocarbon Receptor by Tcdd Prevents Diabetes in Nod Mice and Increases Foxp3 + T Cells in Pancreatic Lymph Nodes - Kerkvliet, Nancy I; Steppan, Linda B; Vorachek, William; Oda, Shannon; Farrer, David; Wong, Carmen P; Pham, Duy; Mourich, Dan V (Immunotherapy, 2009)
The ligand-activated transcription factor, aryl hydrocarbon receptor (AHR), is a novel inducer of adaptive Tregs. 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD), the most potent AHR ligand, induces adaptive CD4+CD25+ Tregs during an acute graft-versus-host (GvH) response and prevents the generation of allospecific cytotoxic T lymphocytes. TCDD also suppresses the induction of experimental autoimmune encephalitis in association with an expanded population of Foxp3+ Tregs. In this study, we show that chronic treatment of NOD mice with TCDD potently suppresses the development of autoimmune Type 1 diabetes in parallel with greatly reduced pancreatic islet insulitis and an expanded population of CD4+CD25+Foxp3+ cells in the pancreatic lymph nodes. When treatment with TCDD was terminated after 15 weeks (23 weeks of age), mice developed diabetes over the next 8 weeks in association with lower numbers of Tregs and decreased activation of AHR. Analysis of the expression levels of several genes associated with inflammation, T-cell activation and/or Treg function in pancreatic lymph node cells failed to reveal any differences associated with TCDD treatment. Taken together, the data suggest that AHR activation by TCDD-like ligands may represent a novel avenue for treatment of immune-mediated diseases.